Development of Scratch-Based Interactive Animation Media on Uniformly Accelerated Rectilinear Motion to Improve Students' Understanding of Concepts - Nia Fitrotul Masulah; Riki Perdana (Universitas Lambung Mangkurat, 2024)
Technological developments impact the learning process as well as the utilization of increasingly creative and innovative learning media. The learning medium becomes essential to the achievement of learning objectives. This study aims to develop scratch-based learning media on uniformly accelerated rectilinear motion material to enhance high school students' concept understanding. The research method used is R&D (Research and Development) with the 4D model (Define, Design, Develop, and Disseminate). Data collection in this study was done by distributing feasibility test questionnaires consisting of three aspects, namely presentation, material, and language, to one expert lecturer in physics education and 13 prospective physics teacher students. Based on the feasibility test results by the validator on the learning medium, the score of each aspect is 3.1, 3.1, and 2.9, with an average score of 3.1 in the feasible category. Therefore, the learning medium that has been developed is feasible to use to increase students' conceptual understanding of uniformly accelerated rectilinear motion material. This study suggests that incorporating scratch-based learning media into other materials can enhance students' comprehension of the subject matter. The recommendations for further research are to test learning media on a large scale at school.